Program Qur’an Digital Tematik: Sebuah Upaya Solutif Merevitalisasi Nilai-Nilai Pendidikan Religius Kepada Remaja di Era Disrupsi - Rochmat, Cecep Sobar; Silfana, Angelica; Sari, Irma Lupita (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
Revitalizing religious values is an effort to revive youth spirituality which is fading due to the dynamics of the rapid flow of disruption in the digital era. Given the phenomenon of moral degradation that is getting worse over time. Based on these symptoms, this research is an effort to revitalize religious values which are felt to have decreased in quality, through the Thematic Digital Qur'an Program as a solutive effort to revitalize the values of religious education for adolescents in the era of disruption. The Thematic Digital Qur'an Program is a digital medium for understanding Islamic teachings quickly and easily. The research method used is quantitative with experimental methods. The subjects of this study were teenagers, amounting to 30 people. The collected data were analyzed using descriptive and inferential analysis techniques. The results of the study show that the experimental method used has succeeded in making changes to adolescents. This is evidenced by the revitalization of the values of youth religious education. The results of inferential analysis with N-Gain analysis show that with the Thematic Digital Qur'an the religious education values of youth in the era of disruption have been revitalized and can become provisions and spiritual capital in fortifying themselves from the phenomenon of moral degradation in the era of disruption. Therefore, revitalizing religious values through the Thematic Digital Qur'an is a solutive step to revive the spirituality of youth in today's digital era.